Asuhan Keperawatan pada Lansia dengan Masalah Ansietas Melalui Penerapan Terapi Relaksasi Otot Progresif di Kecamatan Payung Sekaki - Suci Nurwahyuni; Rina Herniyanti; Ifon Driposwana Putra; Nina Trisnawati (Science: Indonesian Journal of Science, 2025)
Anxiety is a feeling of uncertainty accompanied by feelings of weakness and helplessness caused by an unclear situation and emotional conditions that cause discomfort. One therapy that can be given to elderly people with anxiety problems is progressive muscle relaxation therapy. The goal of this therapy is to provide a positive effect in reducing the range of anxiety. The implementation method used is an experimental technique (treatment) on elderly people with anxiety problems. The number of respondents required is two elderly people with a nursing diagnosis of anxiety. This therapy was carried out for three days from June 13-15, 2025, with a duration of 15-20 minutes. Assessments were carried out using the Hamilton Anxiety Rating Scale (HARS) questionnaire with a pretest and posttest process. There was a significant decrease in anxiety scores for all elderly people after the intervention. The average pretest score ranged from 22-27 (moderate anxiety category), while the posttest score decreased to 8-13 (no anxiety category). This demonstrates the effectiveness of progressive muscle relaxation therapy in reducing anxiety levels.